2022
DOI: 10.1186/s12893-022-01508-z
|View full text |Cite
|
Sign up to set email alerts
|

Hepatobiliary-pancreatic surgery for patients with a prepancreatic postduodenal portal vein: a case report and literature review

Abstract: Background Prepancreatic portal vein (PPV) is a congenital anatomical variant of the portal vein (PV). PPVs are extremely rare and generally classified into two categories, prepancreatic preduodenal portal vein and prepancreatic postduodenal portal vein (PPPV). Prepancreatic preduodenal portal veins are rare, with approximately 100 reported cases globally; PPPVs are even more atypical, with less than 20 documented cases globally. Despite the extremely low occurrence, PPPV knowledge and recognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…6 C). We summarized 15 PPPV cases reported so far [ 6 18 ], including the present case (Table 1 ). Twelve of these 15 cases have been reported in Japan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 C). We summarized 15 PPPV cases reported so far [ 6 18 ], including the present case (Table 1 ). Twelve of these 15 cases have been reported in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, of the 13 PPPV cases for which information on portal vein morphology was provided, seven (53.8%) had irregularly dilated or winding portal vein in the hepatic hilum, and there were five cases with a fragile and thin portal vein wall and firm adhesion with the surrounding tissue. Five of these patients underwent pancreaticoduodenectomy and three underwent combined resection of the portal vein because of difficulty in dissecting the portal vein [ 9 , 16 , 18 ], and two of them had intraoperatively massive bleeding while isolating the portal vein, and thrombosis in the reconstructed portal vein [ 16 , 18 ]. Shimizu et al reported the difficulty of portal vein reconstruction due to the thinness of the portal vein wall and the difficulty of postoperative management due to complications of portal vein thrombosis [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…PPPV was first reported by Brook and Gardner ( 6 ), and a total of 17 cases have been reported to date, including the present case. We have summarized all cases to date and our cases in Table 1 ( 1 , 2 , 5 17 ). Among them, 11 were reported as L-shaped PPPV, while only three were normal-shaped PPPV.…”
Section: Discussionmentioning
confidence: 99%
“…All four cases of L-shaped PPPV had a much thinner venous wall, with close adhesion to pancreas and difficult to isolate. Therefore, three of them underwent PPPV resection and reconstruction after attempting to isolate the PPPV due to intraoperative massive hemorrhage ( 1 , 8 , 15 ), and one case underwent R2 resection with PPPV preserved ( 5 ). In the present case and Tanaka’s report ( 2 ), the normal-shaped PPPV had normal thickness of venous wall and there was a loose tissue area posterior to PPPV and anterior to the pancreatic head which could be isolated safely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation